A Pilot Adaptive Neurofeedback Investigation of the Neural Mechanisms of Implicit Emotion Regulation Among Women With PTSD - Weaver, Shelby S.; Birn, Rasmus M.; Cisler, Josh M. (Frontiers in Systems Neuroscience, 2020)
Posttraumatic stress disorder (PTSD) is widely associated with deficits in implicit emotion regulation. Recently, adaptive fMRI neurofeedback (A-NF) has been developed as a methodology that offers a unique probe of brain networks that mediate implicit emotion regulation and their impairment in PTSD. We designed an A-NF paradigm in which difficulty of an emotional conflict task (i.e., embedding trauma distractors onto a neutral target stimulus) was controlled by a whole-brain classifier trained to differentiate attention to the trauma distractor versus target. We exploited this methodology to test whether PTSD was associated with 1) an altered brain state that differentiates attention towards versus away from trauma cues, and 2) an altered ability to use concurrent feedback about brain states during an implicit emotion regulation task. Adult women with a current diagnosis of PTSD (n=10) and healthy control (n=9) women participated in this task during 3T fMRI. During two initial non-feedback runs used to train a whole-brain classifier, we observed 1) poorer attention performance in PTSD, and 2) a linear relationship between brain state discrimination and attention performance, which was significantly attenuated among the PTSD group when the task contained trauma cues. During the A-NF phase, the PTSD group demonstrated poorer ability to regulate brain states in accordance with attention instructions, and this poorer ability was related to PTSD symptom severity. Further, PTSD was associated with heightened encoding of feedback in the insula and hippocampus. These results suggest a novel understanding of whole-brain states and their regulation that underlie emotion regulation deficits in PTSD.